If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -3) = 26 Reorder the terms: 4(-3 + 2x) = 26 (-3 * 4 + 2x * 4) = 26 (-12 + 8x) = 26 Solving -12 + 8x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 8x = 26 + 12 Combine like terms: -12 + 12 = 0 0 + 8x = 26 + 12 8x = 26 + 12 Combine like terms: 26 + 12 = 38 8x = 38 Divide each side by '8'. x = 4.75 Simplifying x = 4.75
| x^2+2x=40 | | (2-4i)-(3-7i)= | | 12x+8=7x+21 | | 12x+8=9x+21 | | 9x=-15 | | -15-(-14)= | | 66-2x=2x-18 | | 10-9x=40-6x | | 9x-1=7x+14 | | (4x)(4x)+16x= | | 51-6x=12x+23 | | 3+2i+6-5i= | | -2x^2+8x+3=0 | | 3x/5=20 | | 16x^2-36=03 | | x^2(k+1)=156 | | n^2=-4-4 | | -16=-4x-4 | | 3(2x-2)=2(5+x) | | 5x+9=7x | | X^2+5x+4=7.5 | | x^2+x=156 | | 2724.26=1860.46+7h-523.6+92.4 | | 4x-2=12x-79 | | 2x+19=9x+5 | | 6x^2+6=37x | | -8=-4z | | 0.05t=2.3t-6.75 | | 1.8x=36 | | 7h=1860.46-523.6+92.4-2724.26 | | -4m(m+3)=24 | | 4:6=2:5 |